Merriam-Webster's intermediate dictionary - Merriam-Webster, Inc (Springfield, Mass Merriam-Webster, 2004)
aProvides definitions, pronunciation, etymology, part of speech designation, and other appropriate information. Intended for use by students in grades six to eight.^
1 2 4 5 8 11 13 14
Keywords: English language -- Dictionaries